Formation, architecture, and persistence of oral biofilms: recent scientific discoveries and new strategies for their regulation - Lv, Chengyuan; Wang, Ziyi; Li, Zehui; Shi, Xialing; Xiao, Mingming; Xu, Yan (Frontiers in Microbiology, 2025)
Complex microbial interactions occur on the surfaces within the oral cavity, where biofilms form highly organized ecosystems composed of diverse microbial communities and their metabolic products. These biofilms, typically located on the tooth surface or within the gingival sulcus, play a crucial role in both oral and systemic health. Recent studies have significantly improved our understanding of the mechanisms of biofilm formation, their structural characteristics, and their persistence over time. However, the intricate interactions between biofilms and the host, as well as their contributions to both local (e.g., dental caries and periodontitis) and systemic conditions, remain only partially understood. This mini-review summarizes recent scientific progress on the formation, structural dynamics, and ecological functions of oral biofilms. It also highlights emerging strategies for modulating biofilm composition and activity, the regulatory systems governing these interactions, and potential directions for microbiome-based therapies in future research.